Strategic model to enhance students’ entrepreneurship interests through Merdeka Belajar Kampus Merdeka program - Dunggio, Titin; Mashudi, Imam; Darman, Darman (Journal of Educational Management and Instruction (JEMIN), 2024)
The Merdeka Belajar Kampus Merdeka (MBKM) program, launched by Indonesia’s Ministry of Education and Culture in 2020, aims to foster entrepreneurship among university students to address low post-graduation entrepreneurial engagement. A 2022 Tracer Study at Bina Mandiri University Gorontalo (UBMG), Indonesia, found that only 1.13% of 177 alumni pursued entrepreneurship as a profession. Drawing on this issue, this research explores a strategic model to enhance students’ entrepreneurial interests through the MBKM program at UBMG. A qualitative descriptive design was employed, gathering data from key informants, including university leaders, lecturers, and students, through interviews and document analysis. The findings revealed that despite students showing a high potential for entrepreneurship, key barriers such as limited experience and financial capital persist. The study suggests strategies to overcome these challenges, including strengthening practice-based curricula, providing continuous mentorship, fostering positive entrepreneurial mindsets, and encouraging adaptation to external challenges through partnerships with industries and government support. These strategic measures are expected to significantly improve students' entrepreneurial engagement at UBMG.